Heat transfer performance of an integrated solar-air source heat pump evaporator. (15th March 2019) - Long, Jibo; Zhang, Ruichao; Lu, Jiao; Xu, Fu
Highlights: Heat transfer performance of an integrated solar-air source heat pump evaporator was studied. Numerical model was validated experimentally and applied to parametric study. Evaporator water supply can influence the refrigerant evaporation temperature and COP. The coil arrangement significantly affects the air temperature distribution in evaporator. The coil arrangement affects the heat gain capacity of the refrigerant. Abstract: This study proposes a dual heat source integrated heat pump evaporator using solar energy and air energy as the heat sources. Both the refrigerant and water coils were installed and arranged in the evaporator in a certain manner. During the cold season of Xiangtan (China), the heat transfer performance of the integrated heat pump evaporator was studied both experimentally and theoretically (through simulations). The results show that the evaporator's hot water supply can increase the refrigerant's evaporation temperature and heat pump's coefficient of performance (COP). With the increase in average water temperature of evaporator from 14.6 °C to 39.5 °C, the heat pump's COP increased by 15%. In the simulations conditions, the proportions of the heat released by air and the heat released by hot water are basically the same as the experimental date. Comparing the refrigerant-water-refrigerant type evaporator with the water-refrigerant-refrigerant type evaporator, the former is more capable of gaining heat from low temperature water than the latter, and is more conducive to the comprehensive utilization of air and solar energy by heat pump in the cold season. Additionally, the refrigerant-water-refrigerant type evaporator has better anti-frosting capability under lower water temperatures.